Unique gene duplications and conserved microsynteny potentially associated with resistance to wood decay in the Lauraceae - Tian, Xue-Chan; Guo, Jing-Fang; Yan, Xue-Mei; Shi, Tian-Le; Nie, Shuai; Zhao, Shi-Wei; Bao, Yu-Tao; Li, Zhi-Chao; Kong, Lei; Su, Guang-Ju; Mao, Jian-Feng; Lin, Jinxing (Frontiers in Plant Science, 2023)
Wood decay resistance (WDR) is marking the value of wood utilization. Many trees of the Lauraceae have exceptional WDR, as evidenced by their use in ancient royal palace buildings in China. However, the genetics of WDR remain elusive. Here, through comparative genomics, we revealed the unique characteristics related to the high WDR in Lauraceae trees. We present a 1.27-Gb chromosome-level assembly for Lindera megaphylla (Lauraceae). Comparative genomics integrating major groups of angiosperm revealed Lauraceae species have extensively shared gene microsynteny associated with the biosynthesis of specialized metabolites such as isoquinoline alkaloids, flavonoid, lignins and terpenoid, which play significant roles in WDR. In Lauraceae genomes, tandem and proximal duplications (TD/PD) significantly expanded the coding space of key enzymes of biosynthesis pathways related to WDR, which may enhance the decay resistance of wood by increasing the accumulation of these compounds. Among Lauraceae species, genes of WDR-related biosynthesis pathways showed remarkable expansion by TD/PD and conveyed unique and conserved motifs in their promoter and protein sequences, suggesting conserved gene collinearity, gene expansion and gene regulation supporting the high WDR. Our study thus reveals genomic profiles related to biochemical transitions among major plant groups and the genomic basis of WDR in the Lauraceae.